A Outcomes of Vancomycin Enema vs Normal Saline Enema in Patients with Hirschsprung Associated Enterocolitis - Rehan , Muhammad; Gul, Saman; Saleem, Muhammad Salman; Khan, Nasim; Saeed, Khawar (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
OBJECTIVE: This research was designed to compare the outcomes of vancomycin enema and normal saline enema in the treatment of HAEC in terms of full remission of symptoms of HAEC and length of hospital stay. METHODOLOGY: This randomized controlled trial was carried out from March 2020 to March 2021 in the Department of Pediatric Surgery at Lady Reading Hospital Peshawar. A total of 40 patients were randomly assigned in two groups; A (vancomycin enema) and B (normal saline enema), with 20 patients in each group. After the diagnosis was established, patients were randomly assigned to one of two groups by balloting method. SPSS 24 was used for data entry and analysis RESULTS: In our research, males outnumbered females. In both groups, the HAEC score decreased significantly after treatment from pre-treatment scores (12.31 and 11.15) to post-treatment scores (7.73 and 7.61) with significant p –values 0.013 & 0.015 respectively. The average hospital stay between vancomycin enema and normal saline enema group was 7.91 days as opposed to 6.89 days with a p-value (0.031). Overall, 7.33 ± 2.426 days were required for full remission of HAEC symptoms in the study. A p-value of 0.251 suggested that there was no difference between groups in terms of symptom relief CONCLUSION: We conclude that there is no difference between the normal saline and vancomycin enema in terms of symptom resolution and hospital stay in patients of HAEC.